Neem Leaf Glycoprotein Restrains VEGF Production by Direct Modulation of HIF1α-Linked Upstream and Downstream Cascades - Saha, Akata; Nandi, Partha; Dasgupta, Shayani; Bhuniya, Avishek; Ganguly, Nilanjan; Ghosh, Tithi; Guha, Ipsita; Banerjee, Saptak; Baral, Rathindranath; Bose, Anamika (Frontiers in Oncology, 2020)
Neem Leaf Glycoprotein (NLGP) is a natural immunomodulator, have shown sustained tumor growth restriction as well as angiogenic normalization chiefly by activating CD8+ T cells. Here, we have investigated the direct role of NLGP as a regulator of tumor microenvironmental hypoxia and associated vascular endothelial growth factor (VEGF) production. We observed a significant reduction in VEGF level in both in vivo murine tumor and in vitro cancer cells (B16Mel, LLC) and macrophages after NLGP treatment. Interestingly, NLGP mediated VEGF downregulation in tumor cells or macrophages within hypoxic chamber was found at an early 4h and again at late 24h in mRNA level. Our data suggested that NLGP prevented hypoxia-induced strong binding of HIF1α with its co-factors, CBP/p300 and Sp3, but not with Sp1, which eventually limit the binding of HIF1α-transcriptional complex to hypoxia responsive element of VEGF promoter and results a restricted early VEGF transcription. On the otherhand, suppressed phosphorylation of Stat3 by NLGP results reduction of HIF1α at 24h of hypoxia that further support sustained VEGF down-regulation. However, NLGP fails to regulate VHL activity as observed by both in vitro and in vitro studies. Therefore, this study for the first time reveals a mechanistic insight of NLGP mediated inhibition of angiogenesis by suppressing VEGF, which might help in vascular normalization to influence better drug delivery.